Assessment of sanitation service quality in urban slums of Khulna city based on SERVQUAL and AHP model: A case study of railway slum, Khulna, Bangladesh - Md. Shaharier Alam; Mili Mondal (Journal of Urban Management, 2019)
Sanitation facilities are one of the major aspects of an urban area which has paramount importance on the quality of life and environment. The city of Khulna, 3rd largest city of Bangladesh, contains 8.14% slum of total area where poor sanitation facilities exist. Different Government and NGOs provide sanitary latrines in the slums of Khulna city under different sanitation project which hardly meets the demands and expectations of slum people. The present study attempts to assess the urban sanitation service quality of Railway slum of Khulna city based on Customer Satisfaction Index (CSI) where the gap between perception and expectation of the inhabitant of railway slum are evaluated. A combined methodology of SERVQUAL model and Analytical Hierarchy Process is applied in this study for evaluating the gap in term of tangibility, reliability, responsiveness, assurance, and empathy to assess sanitation services in railway slum of Khulna city. The result of CSI indicates that the sanitation service meets moderate satisfaction (58.5%) level of public expectation in railway slum of Khulna city. This combined methodology provides a perspicuous idea of sanitation service quality in a simpler way without any quantitative data requirement which will be helpful in appropriate municipal service planning and management.
Keywords: 710; Analytical Hierarchy Process; Customer Satisfaction Index; Khulna city; Railway sum; Sanitation service quality; SERVQUAL model